The Correlation Between Leg Power Endurance and Arm Power Endurance with Breaststroke Swimming Performance - Muhammad Ramdhani Raja Saputra; Agus Rusdiana; Unun Umaran (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aimed to determine the relationship between leg power endurance and arm power endurance and the performance of the 50-meter breaststroke among athletes of the Tendy Swimming Club. The study employed a quantitative method with a correlational approach. The population and sample consisted of 15 athletes selected using a total sampling technique. The research instruments included the hurdle jump endurance test to measure leg power endurance, the clapping push-up test to measure arm power endurance, and a 50-meter breaststroke swimming test to measure swimming performance. Data analysis was conducted using descriptive statistics, the Shapiro–Wilk normality test, and the Pearson correlation test at a significance level of α = 0.05. The results showed a strong and significant negative relationship between arm power endurance and 50-meter breaststroke performance (r = −0.656; p < 0.05), as well as a very strong and significant negative relationship between leg power endurance and 50-meter breaststroke performance (r = −0.922; p < 0.05). These findings indicate that higher levels of leg and arm power endurance are associated with faster swimming times. Therefore, it can be concluded that leg and arm power endurance have a significant relationship with 50-meter breaststroke performance, with leg power endurance showing a more dominant contribution and requiring special attention in swimming training programs.